Event-Based Tourism and Destination Competitiveness: A Study of the Pandawa Festival at Pandawa Beach, Bali-Indonesia - Ida Ayu Dyana Prawerti; Putu Yunita Wacana Sari; I Gusti Ngurah Putu Dedy Wirawan (Jurnal Internasional Riset Bisnis Pariwisata, 2026)
This study investigates the role of event-based tourism in enhancing destination competitiveness, with a case study of the Semarak Pandawa Festival at Pandawa Beach, Badung, Bali, Indonesia. A sequential exploratory mixed methods design was employed, combining in-depth interviews with five key informants selected through purposive sampling, participatory observation, and a survey of 200 festival visitors using accidental sampling with daily quotas. A 20-item questionnaire adapted from Dwyer and Kim's (2003) destination competitiveness framework measured four dimensions: event attractiveness, visitor experience quality, destination image, and perceived economic value. Findings indicate a combined mean score of 4.13 (high category), confirming the festival's positive contribution to all four dimensions of destination competitiveness. Visitor experience quality recorded the highest score (M = 4.31), while perceived economic value scored lowest (M = 3.87), highlighting price inconsistency and infrastructure limitations as key areas for improvement. This study extends the Dwyer-Kim framework by demonstrating that community-managed cultural festivals serve as core competitive assets in post-pandemic destination recovery, offering applicable insights for event-based destination management.